Effect of double-pulse-laser polarization and time delay on laser-assisted etching of fused silica. (27th October 2017) - Chu, Dongkai; Sun, Xiaoyan; Dong, Xinran; Yin, Kai; Luo, Zhi; Chen, Guowei; Duan, Ji-An; Hu, Youwang; Zhao, Xinyu
Abstract: High-aspect-ratio microchannels were fabricated by femtosecond-double-pulse-laser-assisted polarization-selective etching. The etching rate and uniformity of the microchannels were mainly determined by the double-pulse polarization and time delay. We found that when the two sub-pulses had a different polarization (one linear, the other circular), the microchannel etching rate increased by a factor of 10 compared to when both sub-pulses were linearly polarized. The maximum etching rate was obtained when the polarization combination was circular for the first sub-pulse and vertical for the second one. In this case, the etching rate was independent from the time delay. Laser confocal microscopy images showed that when the polarization was circular, the area modified by the laser was larger than when the polarization was linear, explaining the higher etching rate value obtained after irradiation with circularly polarized laser light.